2000
DOI: 10.1046/j.1525-1373.2000.22429.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-Protein Diet Changes Thyroid Function in Lactating Rats

Abstract: Lactating rats were fed with free access to an 8% protein-restricted diet (PR); the control group was fed a 23% protein diet (C). An energy-restricted (pair-fed) group was given the same food as the animals in the control group, but the amounts of food consumed by both PF and PR were about the same. The body weight and serum albumin concentration of PR and PF dams were significantly (P < 0. 05) lower than that of the controls. The PR group had a significant increase in serum-free triiodothyronine (FT3) concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 41 publications
3
25
1
3
Order By: Relevance
“…The same alteration was also described in animals that received a cafeteria diet (14,16) or protein-and energy-restricted diets (12,28,29). Furthermore, since the high-fat diet is instituted abruptly during the third week of gestation, the novelty of the diet could create a food avoidance behavior that could explain the early reduction of food ingestion.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The same alteration was also described in animals that received a cafeteria diet (14,16) or protein-and energy-restricted diets (12,28,29). Furthermore, since the high-fat diet is instituted abruptly during the third week of gestation, the novelty of the diet could create a food avoidance behavior that could explain the early reduction of food ingestion.…”
Section: Discussionmentioning
confidence: 53%
“…We have shown that protein-restricted diets lead to a decrease in 131 I thyroid uptake and to higher serum TSH and lower T 4 concentrations, but surprisingly the animals in that study (12) had higher serum T 3 concentrations due in part to a higher thyroid T 4 to T 3 conversion (33). In contrast, energy-restricted mothers had no change in thyroid radioiodine uptake and lower serum TSH, T 4 and T 3 concentrations.…”
Section: Control Diet Groupmentioning
confidence: 60%
See 2 more Smart Citations
“…Our previous studies showed short-and long-term effects of malnutrition during lactation on the thyroid function of mothers and their offspring (Ramos et al 2000, Passos et al 2001a,b, 2002. Dams submitted to a proteinrestricted (PR) diet during lactation had, at weaning, a significant decrease in 131 I thyroid uptake and an increase in 131 I uptake by the mammary gland and a higher transfer of 131 I to the milk when compared with controls (Ramos et al 2000). These animals had higher tri-iodothyronine (T 3 ) levels in serum and milk, and lower serum levels of thyroxine (T 4 ) during lactation (Passos et al 2001a).…”
Section: Introductionmentioning
confidence: 99%